THE DEVELOPMENT OF DIGITAL-BASED ECONOMIC TEACHING MATERIALS FOR SMA ANANDA BATAM - Kennardi Tanujaya; Chrislin Chrislin (Universitas Internasional Batam, 2022)
Since the Covid-19 pandemic, all human activities have undergone major changes. Among them are teaching and learning activities that should be done face-to-face, are now conducted online. The lack of teaching resources in the Covid-19 era triggered the implementation of community service activities at SMA Ananda Batam. This activity aims to help teachers by compiling digital teaching materials according to the needs of SMA Ananda Batam. This activity is carried out by interviewing teachers to learn about the problems faced by teachers. Through interviews conducted, it is known that digital teaching materials for Economics class X are in need, thus the output for this activity is in the form of digital teaching materials for class X Economics in the form of teaching module, powerpoints, question banks and solution banks, and presentation video. Digital teaching materials that are in line with the school curriculum are very beneficial for SMA Ananda Batam because they can make online teaching and learning activities more efficient and the subjects offered can be more easily understood by students. The recommendations for the next community service activity are to create new innovations, such as quizzes in the form of games and animated videos so that students are more active in online teaching and learning activities.